Mitochondrial DNA duplication, recombination, and introgression during interspecific hybridization - Silvia Bágeľová Poláková (Nature Portfolio, 2021)
Abstract mtDNA recombination events in yeasts are known, but altered mitochondrial genomes were not completed. Therefore, we analyzed recombined mtDNAs in six Saccharomyces cerevisiae × Saccharomyces paradoxus hybrids in detail. Assembled molecules contain mostly segments with variable length introgressed to other mtDNA. All recombination sites are in the vicinity of the mobile elements, introns in cox1, cob genes and free standing ORF1, ORF4. The transplaced regions involve co-converted proximal exon regions. Thus, these selfish elements are beneficial to the host if the mother molecule is challenged with another molecule for transmission to the progeny. They trigger mtDNA recombination ensuring the transfer of adjacent regions, into the progeny of recombinant molecules. The recombination of the large segments may result in mitotically stable duplication of several genes.